2019
DOI: 10.1590/1808-057x201806020
|View full text |Cite
|
Sign up to set email alerts
|

Do I win, does the company win, or do we both win? Moderate traits of the Dark Triad and profit maximization

Abstract: This article analyzes the relationship between the maximization of personal and company gains and the moderate traits of the Dark Triad. The relevance of choosing this topic lies in investigating the attitude of executives who exhibit characteristics of a moderate intensity between the strong and weak traits. It is proven that the vision and charisma of narcissistic individuals, the strategy and tactics of Machiavellian individuals, and the creativity and good strategic thinking of psychopathic individuals are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
1
10
0
5
Order By: Relevance
“…Other Brazilian investigations included narcissism as a topic of study, but used other research instruments, with a different score to verify the disposition for the dark trait. D’Souza, Lima et al (2019) and D’Souza and Lima (2015) used the short dark triad (SD3; Jones and Paulhus, 2014) to collect nine Likert-type statements (1–5 points) regarding disposition to narcissistic traits. The authors found mean truex¯ = 2.8 with managers and truex¯ = 3.01 with Master in Business Administration (MBA) students, respectively.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other Brazilian investigations included narcissism as a topic of study, but used other research instruments, with a different score to verify the disposition for the dark trait. D’Souza, Lima et al (2019) and D’Souza and Lima (2015) used the short dark triad (SD3; Jones and Paulhus, 2014) to collect nine Likert-type statements (1–5 points) regarding disposition to narcissistic traits. The authors found mean truex¯ = 2.8 with managers and truex¯ = 3.01 with Master in Business Administration (MBA) students, respectively.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…As for the studies that discuss the narcissistic personality trait related to decision-making, the results show that individuals with high traits of narcissism demonstrate impulsiveness and overconfidence in their knowledge and performance by agreeing with risky bets that could result in victory and success, even though they know that the consequences can be harmful to the company (Lakey, Rose, W. K Campbell, & Goodie, 2008; W. K Campbell, Goodie, & Foster; 2004; WK, Campbell, Hoffman, SM Campbell, & Marchisio, 2011), because the courage for risky decisions comes from the need for praise when business performance is higher than expected (Chatterjee & Hambrick, 2011).…”
Section: Theoretical Framework and Development Of Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Estudos no âmbito comportamental sugerem que a prática de manipular resultados é motivada pela personalidade dos indivíduos (Silva, 2019;D'Souza, Lima, Jones, & Carre, 2019;Góis, 2017;D'Souza, 2016;D'Souza & Lima, 2015) porque, como enuncia a teoria do Alto Escalão (Hambrick, 2007;Hambrick & Mason, 1984), as interpretações e escolhas de executivos estão relacionadas às características pessoais, aos valores e à personalidade.…”
Section: Introductionunclassified